Verification of the Prerequisite Programs and HACCP System Applied in some Chicken Products Factories in Makah Al-Mukarramah KSA - Abumalih, Adel Mohammed; Madkour, Mohamed Hussein; Abd El-Razik, Mohamed Moustafa (Journal of agricultural, environmental and veterinary sciences, 2022)
Hazard Analysis Critical Control Point (HACCP) is a vital tool and preventative approach to ensuring the safety of food processing to produce safe food for the consumer. Therefore, in this proposal, an accurate and broad model of the HACCP system has been developed to develop the safety of consumption and quality of chicken products that are manufactured in six chicken products factories at Makkah Al Mukarramah - Kingdom of Saudi Arabia. This study was based on the good health applications for manufacturing (GHP) in poultry meat factories, and the application of safe food systems such as good manufacture applications (GMP), ISO 22000 Quality Systems for Manufacturing, and the HACCP system, which are used to verify what is known as the qualitative methodology. The factories under study were classified, as four factories represented the highest ratings (A) which are SUP, SUN, AMK, AAQ88, while the SHA77 factory achieved the (B) rating, and the NAS66 factory achieved the lowest rating (C). The application of the HACCP system has been verified in the factories under study taking into account all the HACCP factors such as verification procedures, critical control point control requirements, record keeping, flow chart, and corrective actions. Six critical control points (CCPs) in the manufacture of frozen chicken breast fillet product in the studied factories were identified and documented. The most important critical control points that were identified were the cold stores, the X-ray inspection area during the inspection of undesirable materials in the final product, the cooking area, the unwanted foreign metal detection area, the area of the loading and transport warehouses, and corrective actions were identified in cases of non-conformance. Therefore, the researcher recommends the necessity of applying the HACCP system in all poultry meat processing factories in the Kingdom to achieve the comprehensive quality content for the consumer.
Keywords: Food Safety; Hazard Control Critical Analysis Point; poultry products factories